AB0794 CLINICAL TRIAL DISCRIMINATION OF PHYSICAL FUNCTION INSTRUMENTS FOR PSORIATIC ARTHRITIS: A SYSTEMATIC REVIEW. (13th June 2020) - Leung, Y. Y.; Holland, R.; Mathew, A.; Lindsay, C.; Goel, N.; Ogdie, A.; Orbai, A. M.; Hoejgaard, P.; Chau, J.; Coates, L. C.; Strand, V.; Gladman, D. D.; et al.
Abstract : Background: Physical function is a core domain to be measured in randomized controlled trials (RCTs) of psoriatic arthritis (PsA). The discriminative performance of patient reported outcome measures (PROMs) for physical function (PF) in RCTs has not been evaluated systematically. Objectives: In this systematic review, the GRAPPA-OMERACT working group aimed to evaluate the clinical trial discrimination of PF-PROMs in PsA RCTs. Methods: We searched PubMed and Scopus databases in English to identify all original RCTs conducted in PsA. We limited the review to RCTs of biologic and targeted synthetic DMARDs. Groups of two researchers extracted data independently for PF-PROMs. We assessed quality in each article using the OMERACT good method checklist. Effect sizes (ES) for the PF-PROMs were calculated and appraised using a priori hypotheses. Evidence supporting clinical trial discrimination for each PF-PROM was summarized to derive recommendations. Results: 32 articles were included (Figure 1 ). Four PF-PROMs had data for evaluation: HAQ-Disability Index (DI), HAQ-Spondyloarthritis (S), Short Form 36-item Health Survey Physical Component Summary (SF-36 PCS), and the Physical Functioning domain (SF-36 PF) (Table 1 ). The ES for intervention versus (vs.) control arms for HAQ-DI ranged from -0.55 to -1.81 vs. 0.24 to -0.52; and for SF-36 PCS ranged from 0.30 to 1.86 vs. -0.02 to 0.63. Conclusion: Clinical trial discrimination was supported for HAQ-DI and SF-36 PCS in PsA with low risk of bias; and for SF-36 PF with some caution. More studies are required for HAQ-S. Disclosure of Interests: Ying Ying Leung Speakers bureau: Novartis, Janssen, Eli Lilly, Richard Holland: None declared, Ashish Mathew: None declared, Christine Lindsay Employee of: Previously employed (worked) for pharmaceutical company., Niti Goel Shareholder of: UCB and Galapagos, Consultant of: VielaBio, Mallinckrodt, and IMMVention, Alexis Ogdie Grant/research support from: Novartis, Pfizer – grant/research support, Consultant of: AbbVie, BMS, Eli Lilly, Novartis, Pfizer, Takeda – consultant, Ana-Maria Orbai Grant/research support from: Abbvie, Eli Lilly and Company, Celgene, Novartis, Janssen, Horizon, Consultant of: Eli Lilly; Janssen; Novartis; Pfizer; UCB. Ana-Maria Orbai was a private consultant or advisor for Sun Pharmaceutical Industries, Inc, not in her capacity as a Johns Hopkins faculty member and was not compensated for this service., Pil Hoejgaard: None declared, Jeffrey Chau: None declared, Laura C Coates: None declared, Vibeke Strand: None declared, Dafna D Gladman Grant/research support from: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – grant/research support, Consultant of: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – consultant, Robin Christensen: None declared, William Tillett: None declared, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau